Observation of the hepatoprotective and antioxidant activities of Trianthema decandra Linn. (Vallai sharunnai) roots on carbon tetrachloride-treated rats - G. Balamurugan; P. Muthusamy (Bangladesh Pharmacological Society, 2008)
The present study was carried out to observe the hepatoprotective effect and antioxidant activity of the ethanol extract of the roots of Trianthema decandra Linn. (200 and 400 mg/kg) in rats treated with carbon tetrachloride for 8 weeks. Extract at the tested doses restored the levels of all serum (aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total bilirubin and total protein) and liver homogenate enzymes (glutathione peroxidase, glutathione reductase, superoxide dismutase and catalase) significantly. Histology demonstrated profound steatosis degeneration and nodule formation were observed in the hepatic architecture of carbon tetrachloride treated rats which were found to acquire near-normalcy in extract plus carbon tetrachloride administrated rats, and supported the biochemical observations. This study suggests that ethanol extract of T. decandra has a liver protective effect against carbon tetrachloride- induced hepatotoxicity and possess antioxidant activities.